RANCANG BANGUN APLIKASI PEMANTAUAN AKTIVITAS PADA KOMPUTER BERBASIS ANDROID - Junaedy; Hamdan Arfandy (STMIK KHARISMA Makassar, 2017)
This study aims to utilize android based applications in designing and building applications that can assist parents in monitoring computer activities operated by his son. In the process of making this application, the author uses Juno Eclipse with Java programming language. Testing methods used writer is black box testing. As a result, it can be stated that the system has been created by the author goes according to plan and specification requirements. Based on the results of this study concluded that the author has managed to create android based mobile application to assist in the monitoring of the activity on the computer.